ESSENCE AND CONCEPTS OF FINANCIAL RESOURCES OF THE ENTERPRISE (World Economics and Finance Bulletin, 2023)
This article explores the essence of the concept of "financial resources of an enterprise" at the macro and micro levels, improves their definition as an economic category. The components and structure of sources of financial resources are determined, the expediency of their use is justified. The purpose of the article is to study essence of the concept and composition of financial resources of the enterprise, as well as the study of problems associated with their formation
Keywords: financial resources; the sources of financial resources; structure of financial resources of the enterprise